THE CONTENT AND SPECIFIC FEATURES OF THE LEGAL INSTITUTION OF TORT LAW (Modern American Journal of Social Sciences and Humanities, 2026)
This article scientifically analyzes the theoretical foundations of tort law and its role in the system of civil liability. It covers the legal nature of negligent and intentional offenses, their main elements - the duty of care, violation of this duty, causal connection, and the existence of damage. It also reveals the importance of tort law in protecting personal non-property and property rights, the content of the mechanism for recovering damages, and its role in ensuring justice and balance in civil transactions. The article summarizes the importance of tort law in the modern legal system and its role in regulating legal relations.